A Story of the [Re] Construction of a Research Setting for an Ethnographical Study of Accounting Practices in an Indonesia Listed Company - Rasyid, Eddy R; Gaffikin, Michael JR (The International Journal of Accounting and Business Society, 1996)
In the recent accounting case study literature, a story of the construction of the research field is missing. It make the readers unable to gain an understanding of the local nuances of the field where the research takes place at the time of the presence of the researcher. As such, the readers have been made unable to develop better their own understanding of the research reports being presented is not separated from her/his research, the story o access construction is needed to be accounted as an integral part o the tales of the field. This paper provides an illustrative story o how such an access construction process has been acquired a careful attention b the researcher.